2008
DOI: 10.1177/0011128707309997
|View full text |Cite
|
Sign up to set email alerts
|

Interdistrict Disparity in Sentencing in Three U.S. District Courts

Abstract: Research examining disparities in sentencing outcomes under federal sentencing guidelines has focused almost exclusively on aggregate national data. Although these studies contribute considerably to the criminological literature on sentencing disparity, their findings may have masked contextual variation in relation to case processing across jurisdictions. With data from the U.S. District Courts for Minnesota, Nebraska, and Southern Iowa for 1998 through 2000, this article assesses whether interdistrict variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 43 publications
1
35
1
1
Order By: Relevance
“…Researchers have noted that sampling selection bias can be problematic in OLS regression analyses since observations are not selected independent of the outcome of interest, specifically that only defendants sent to prison will have a sentence length outcome. Previous studies have utilized the Heckman (1974) two-step procedure as a remedy (see for instance Engen & Gainey, 2000;Steffensmeier et al, 1998;Steffensmeier & Demuth, 2000;Wu & Spohn, 2010). Bushway, Johnson, and Slocum, (2007), however, contend that this is not always an appropriate remedy for selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have noted that sampling selection bias can be problematic in OLS regression analyses since observations are not selected independent of the outcome of interest, specifically that only defendants sent to prison will have a sentence length outcome. Previous studies have utilized the Heckman (1974) two-step procedure as a remedy (see for instance Engen & Gainey, 2000;Steffensmeier et al, 1998;Steffensmeier & Demuth, 2000;Wu & Spohn, 2010). Bushway, Johnson, and Slocum, (2007), however, contend that this is not always an appropriate remedy for selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…Some research has controlled for citizenship status in multivariate models of sentencing outcomes with mixed results. Some studies reveal no significant effects on sentence length (Wu & Spohn, 2010), while others conclude both increased odds of incarceration and lengthier sentences for citizens (Johnson & Betsinger, 2009). Similarly, studies reveal that non-citizens are less likely to receive substantial assistance departures (Spohn & Fornango, 2009), but more likely to receive judicial downward departures (Johnson & Betsinger, 2009).…”
Section: Determinants Of Sentencingmentioning
confidence: 99%
“…If reforms inadvertently gave more discretionary power to prosecutors (who determine the severity of charges filed), it might reproduce or exacerbate the racial bias the reforms were intended to address and help to explain the findings in this study (Hartley, Maddan, & Spohn, 2007;Kempf-Leonard & Sample, 2001;Wu & Spohn, 2008). A few studies have found that prosecutors are more likely to take into consideration factors outside of the offender's crime and prior record (directly or indirectly associated with race and/or other factors) in determining prosecution of property and other nonviolent felony cases but less likely for violent crimes (Engen et al, 2003;Ulmer, Kurlychek, & Kramer, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Prosecutorial discretion may explain the increased disparity in imprisonment, but this of course cannot be tested with the macro-level data in this analysis and would be best understood with micro-level data. Wu and Spohn (2008), for example, found in an analysis of three U.S. district courts that considerable variation exists from court-to-court and individual-to-individual and that context is important in understanding the differences.…”
Section: Discussionmentioning
confidence: 99%